The use of horizontal force-velocity profile in soccer: a rapid systematic review - Adam Lipčák; Lucie Lipková; Tomáš Kalina; Marcos Michaelides; Koulla Parpa; Ana Carolina Paludo (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background The ability to accelerate and reach high sprinting velocities is crucial to soccer performance. In this context, the horizontal force-velocity profile (H-FVP) has emerged as a tool to evaluate neuromuscular capabilities relevant to sprinting. This rapid review aims to critically describe the application of H-FVP in soccer and summarize the characteristics of the methodologies employed in its measurement and calculation. Methods A rapid systematic review was conducted in accordance with the Cochrane Rapid Reviews Guidance and PRISMA guidelines. A search on MEDLINE (via PubMed), SPORTDiscus (via EBSCOhost), and Web of Science databases was conducted in February 2025. Studies were considered eligible if they assessed the H-FVP in soccer players of any competitive level and both sexes. Results Fourteen studies met the inclusion criteria, analysing a total of 1320 soccer players across different competitive levels. Most studies explored the relationship between H-FVP parameters and sprint or change of direction performance. Additional studies addressed variations according to playing position differences, biological maturation, fatigue responses, or injury profile. The predominant testing protocols involved linear sprints ranging from 30 to 40 m, often with split-distance measurements. The Samozino method was consistently used for H-FVP computation. Commonly reported parameters included theoretical maximal force (F0), velocity (V0), and power (Pmax), with some studies also including the ratio of force (RF) and its decrease with speed (DRF). Radar devices, photocell systems and mobile applications were the primary measurement tools utilized. Conclusion This systematic review highlights the potential of the H-FVP as an approach to be used to improve sprint performance in soccer players across competitive levels. However, methodological inconsistencies among studies highlight the need for standardized testing protocols to improve their practical application. Identified gaps in the literature point out the necessity for further investigation in future research.